The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/08916150701815796
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Treated Titanium Balls for the Mitigation of Mineral Fouling in Heat Exchangers

Abstract: The present study investigated the feasibility of a physical water treatment (PWT) concept using heat-treated titanium balls for the mitigation of mineral fouling in heat exchangers. A concentric tube heat exchanger in a counter-flow set-up served as the test section, where three different velocities (i.e., 0.3, 0.5, 0.8 m/s) were used for the fouling tests. The results showed that for the PWT cases fouling resistances were 24-30% lower than those for the untreated cases, depending on the flow velocity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Aragonite has a specific gravity of 2.95 while calcite has 2.71. The orthorhombicshaped and denser aragonite tends to be more adherent to heat transfer surfaces than the hexagonal-shaped calcite [6,16]. The chemical reaction for the precipitation of CaCO 3 is found in the literature [3,4,16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aragonite has a specific gravity of 2.95 while calcite has 2.71. The orthorhombicshaped and denser aragonite tends to be more adherent to heat transfer surfaces than the hexagonal-shaped calcite [6,16]. The chemical reaction for the precipitation of CaCO 3 is found in the literature [3,4,16].…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have been reported for the effectiveness of the use of permanent magnets [3,4,8,11,[17][18][19][20], solenoid coils [3,4,8,[21][22][23][24], catalytic materials like copper, zinc [25,26], and titanium [16], and ultrasounds [10]. In this paper, RF (radio frequency) electric fields generated between two graphite electrode plates directly in water were used to mitigate mineral fouling in a doublepipe heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…The problems on production safety and equipment maintenance caused by calcium carbonate scale have becoming increasingly serious. Calcium carbonate is an inversely soluble salt [1], that is, its solubility decreases with increasing temperature. Calcium and carbonate ions in the circulating cooling water combine to form calcium carbonate scale and are deposited on the surface of heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…Scale inhibition methods are mainly classified into chemical and physical techniques. The former generally has disadvantages, such as high cost and secondary pollution to the environment [2,6], whereas the latter is economic and environmentally friendly [1,2,6,[8][9][10][11]. Hence, physical water treatments may replace chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional physical descaling methods such as scraping, sand blasting, and metal or nylon brushing incur downtime and repair costs [9]. For these reasons, new physical methods such as electronic anti-fouling technology, catalytic material, and sudden pressure change have recently been developed [5][6][7].…”
mentioning
confidence: 99%